Research and Technical Change in the Pharmaceutical Industry - Comanor, William S. (The Review of Economics and Statistics, 1965)
IN recent years there has been a good deal of discussion concerning the relationships among market structure, research and development, and the rate of technical change. Much of this discussion has focussed on the question of whether large firm size is a necessary condition before firms will engage in research, and whether research and development (R and D) is likely to grow more or less than in proportion to increases in firm size. A further set of questions deals with the relationship between research and the rate of technical change experienced by the firm. Can variation in the latter be explained largely by differences among firms in the size and character of their research programs? Are economies of scale in R and D likely to be present? What is the effect of firm size on the productivity of a research establishment? This paper provides an empirical analysis, concerned with these questions, of the experience of the United States pharmaceutical industry during the period between 1955 and 1960.